1988
DOI: 10.1101/gad.2.8.957
|View full text |Cite
|
Sign up to set email alerts
|

A liver-specific factor essential for albumin transcription differs between differentiated and dedifferentiated rat hepatoma cells.

Abstract: We have identified and characterized two mutually exclusive nuclear proteins that interact with a single crucial element of the albumin promoter. One, albumin proximal factor (APF), is found only in liver or differentiated hepatoma cells and is probably identical to the liver-specific factors named HNFl, alTFB, or HPl-binding protein. The other, variant albumin proximal factor (vAPF), is present in dedifferentiated hepatoma cells as well as in somatic cell hybrids that show extinction of the expression of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
236
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(250 citation statements)
references
References 52 publications
13
236
1
Order By: Relevance
“…HNF-1beta is a transcription activator that regulates the promoters or enhancers of genes that are expressed in a liver-specific manner, such as albumin and alpha-fetoprotein. [16][17][18] In normal tissue, HNF-1beta is expressed not only in the liver, but also in the digestive tract, pancreas, and kidney, where it plays a role as a major regulator of glucose homeostasis. 19 It has been shown that the reduction of HNF-1beta expression by RNA interference induced apoptosis in ovarian clear cell carcinoma cell lines, suggesting that HNF-1beta expression is essential for the survival of clear cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…HNF-1beta is a transcription activator that regulates the promoters or enhancers of genes that are expressed in a liver-specific manner, such as albumin and alpha-fetoprotein. [16][17][18] In normal tissue, HNF-1beta is expressed not only in the liver, but also in the digestive tract, pancreas, and kidney, where it plays a role as a major regulator of glucose homeostasis. 19 It has been shown that the reduction of HNF-1beta expression by RNA interference induced apoptosis in ovarian clear cell carcinoma cell lines, suggesting that HNF-1beta expression is essential for the survival of clear cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several different structures of doublestranded DNA, including unmodified oligonucleotide duplexes, ab-anomeric oligonucleotides, phosphorothioate oligonucleotide duplexes and dumbbell oligonucleotides, have been introduced as decoys for transcription factors. [1][2][3][4][5][6][7][8] The main limitation of unmodified ODN is relatively easy degradation by nucleases prevalent in sera and cells. To rectify this problem, ODNs with modified linkages, such as phosphorothioate and methylphosphonate, were developed.…”
Section: Introductionmentioning
confidence: 99%
“…The revertants (Rev7 cells), which occur at a frequency of 10 -9 , express nearly all of the liver-specific proteins and are morphologically similar to the original differentiated cells (Deschatrette et al 1980), perhaps because cells need several hepatocyte-specific proteins to perform gluconeogenesis and grow in media without glucose. Although the original differentiated Fao cells expressed the 88-kD form of HNF-1 found in liver extracts, the C2 cells expressed a 68-kD variant form of HNF-1 (vHNF-1) that exhibited DNA sequence specificity identical to the original HNF-1 protein Cereghini et al 1988). The Rev7 revertant cells expressed the 88-kD form of HNF-1 as well as the entire group of HNF-l-dependent genes.…”
mentioning
confidence: 99%
“…Furthermore, we find that heterodimerization is regulated in a tissue-specific manner, as freely exchangeable heterodimers are formed in transfected Jurkat human T cells but stable nonexchangeable homodimers are present in liver extracts. For simplicity we will use the terms HNF-I~ for the original HNF-1 protein (Courtois et al 1987) and HNF-I~ for the newly cloned vHNF-1 Cereghini et al 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation